Improving magnetic resonance imaging (MRI) examinations: Development and evaluation of an intervention to reduce movement in scanners and facilitate scan completion. (2nd February 2015) - Powell, Rachael; Ahmad, Mahadir; Gilbert, Fiona J.; Brian, David; Johnston, Marie
<x xml:space="preserve">Abstract</x> Objectives The movement of patients in magnetic resonance imaging (MRI) scanners results in motion artefacts which impair image quality. Non‐completion of scans leads to delay in diagnosis and increased costs. This study aimed to develop and evaluate an intervention to enable patients to stay still in MRI scanners (reducing motion artefacts) and to enhance scan completion. Successful scan outcome was deemed to be completing the scan with no motion artefacts. Design and methods Previous research indicated self‐efficacy to predict successful scan outcome, and interviews with patients identified a need for procedural and sensory information to facilitate successful scan behaviour. A DVD intervention was developed which targeted self‐efficacy and included procedural and sensory information. It was successfully piloted with 10 patients and then evaluated in a randomized controlled trial compared with the standard hospital information leaflet (intervention group N = 41; control group N = 42). The clinic radiographer, who was blind to group allocation, rated MRI scans for motion artefact and recorded whether the participant completed the scan; participants completed MRI self‐efficacy and anxiety measures. Results Only one participant reported not finding the DVD useful. Thirty‐five participants in the intervention group and 23 in the control group completed scans and had no motion artefacts, χ2(1, 83) = 7.84, p < .001 (relative risk of an unsatisfactory outcome in the control group/intervention group = 3.09). The intervention effect was mediated by self‐efficacy. Conclusions The DVD intervention was efficacious and warrants further research to examine generalizability. <boxed-text content-type="box" id="bjhp12132-blkfxd-0001" position="anchor" orientation="portrait"> Statement of contribution What is already known on this subject? Motion artefacts and scan incompletion result in repeat scans, delay in diagnosis, and increased health care costs. Self‐efficacy predicts successful scan behaviour (completion of the scan without motion artefact). What does this study add? The development of a theory‐ and evidence‐based intervention targeting self‐efficacy is described. The intervention was acceptable and efficacious in improving scan behaviour. The intervention has potential to be routinely implemented; it is easy to administer and low in cost. </boxed-text>